THE ROLE OF BUZZERS ON SOCIAL MEDIA IN SHAPING ISSUES DURING THE 2024 WEST SUMATRA (WEST SUMATRA) REGIONAL ELECTIONS - Rinaldi, Rinaldi; Dalmenda, M.A.; Arifuddin, M. Thaufan (Jurnal Ranah Komunikasi, 2024)
This study aims to analyze the pattern of issue formation and narratives that developed on social media during the implementation of the West Sumatra (West Sumatra) Regional Head Election (Pilkada) in 2024. The main focus of this research is to identify how key issues are raised and processed in conversations on social media and to understand the role of key actors in shaping political narratives. Content analysis methods and social networks are used to study patterns of interaction and information distribution on various social media platforms. The results show that certain issues are more prominent in influencing public opinion and get high user engagement, especially on themes related to local identity, regional policies, and political party dynamics. This finding is expected to contribute to understanding political dynamics in the digital era and the impact of social media on the formation of public opinion during the Regional Election process. In addition, the results of this research can be a reference for the government, political practitioners, and the public in managing political issues and narratives that develop on social media.